2022
DOI: 10.3389/fcimb.2022.821662
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Live Combined Bacillus subtilis and Enterococcus faecium on Gut Microbiota Composition in C57BL/6 Mice and in Humans

Abstract: Probiotics, prebiotics, and synbiotics can alleviate metabolic syndrome by altering the composition of the gut microbiota. Live combined Enterococcus faecium and Bacillus subtilis has been indicated to promote growth and reduce inflammation in animal models. However, the modulatory effects of live combined B. subtilis R-179 and E. faecium R-026 (LCBE) on human microbiota remain unclear. The current study examined the growth of these two strains in the presence of various oligosaccharides and assessed the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…There is growing evidence for a positive correlation between the Firmicutes to Bacteroidetes (F/B) ratio and metabolic syndrome and hyperlipidemia in both human and mouse models. 37 Our results showed that the F/B ratio was significantly higher in the HFD group compared to that in the Con group. The F/B ratio was significantly lower in the HFD + GBR group relative to the HFD group.…”
Section: Papermentioning
confidence: 46%
“…There is growing evidence for a positive correlation between the Firmicutes to Bacteroidetes (F/B) ratio and metabolic syndrome and hyperlipidemia in both human and mouse models. 37 Our results showed that the F/B ratio was significantly higher in the HFD group compared to that in the Con group. The F/B ratio was significantly lower in the HFD + GBR group relative to the HFD group.…”
Section: Papermentioning
confidence: 46%
“…It contributes to enhanced digestion by providing enzymes, antimicrobial peptides, and other advantageous metabolic byproducts, which collectively improve feed efficiency, growth performance, and the integrity of the gut barrier [ 46 , 47 ]. B. subtilis also plays a pivotal role in modulating the intestinal microbiota and the immune response, thereby warding off pathogenic microorganisms and preventing diseases [ 48 , 49 , 50 ]. In addition, B. subtilis is often employed as an engineering bacterium for the efficient expression of exogenous proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a balanced diet may help prevent Escherichia-Shigella proliferation and be a potential prophylactic measure for individuals with a genetic predisposition to IgAN. In addition, hyperlipidemia is one of the most common comorbidities that increases the risk of progression to ESKD 43 in patients with IgAN, whereas the reduction of cholesterol was reportedly accompanied by a marked decrease of Escherichia-Shigella 48 . Essential fatty acid deficiency was also a hallmark of patients with IgAN, 49 which may be attributed to the alteration of gut microbiota, with evidence of strengthened fatty acid degradation, unsaturated fatty acid biosynthesis, or glycerophospholipid metabolism.…”
Section: Discussionmentioning
confidence: 99%